The Influence of Leverage, Managerial Ownership, Liquidity, and Firm Size on Financial Performance in Basic Materials Companies Listed on the Indonesia Stock Exchange - Nurhadiyanti, Vivi; Suryadi, Edy (GoAcademica Research & Publishing, 2024)
The study aims to explore the significant influence of leverage, managerial ownership, liquidity, and firm size on financial performance, as assessed through DAR (Debt to Asset Ratio), managerial ownership levels, CR (Current Ratio), LN (natural logarithm), and ROA (Return on Asset). The research sample comprises 89 companies that were listed on the Indonesia Stock Exchange between 2020 and 2022, including those submitting annual financial reports for the same period. Purposive sampling was employed in selecting the sample. Data analysis relied on secondary data obtained through documentation methods. The audited financial reports sourced from the Indonesia Stock Exchange's official website served as the research data. The concurrent findings of the study indicate that the effects of business size, liquidity, managerial ownership, and leverage are negligible. Partial results suggest that, collectively, the independent variables do not significantly impact the dependent variable.